2001
DOI: 10.1007/s001250100007
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous abdominal, but not femoral fat expression of plasminogen activator inhibitor-1 (PAI-1) is related to plasma PAI-1 levels and insulin resistance and decreases after weight loss

Abstract: Plasminogen activator inhibitor-1 (PAI-1) is the main inhibitor of tissue-type plasminogen activator and has an important role in regulating the fibrinolytic system and thrombus formation. Higher plasma PAI-1 concentrations impair fibrinolysis, which could account for its predictability for cardiovascular events [1,2]. Obesity, an independent risk factor for cardiovascular diseases is associated with increased plasma PAI-1 values [3,4].The mechanisms involved in increased PAI-1 production in obesity have not b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
1
3

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(79 citation statements)
references
References 22 publications
3
72
1
3
Order By: Relevance
“…Our 1-year results are in accordance with those previously obtained in a Swedish study [20]. In connection with the weight decline, our subjects' insulin sensitivity improved, which may partly explain the reduction in PAI-1 [30]. Surprisingly, there is one lifestyle intervention study in which marked weight loss and a decrease in insulin resistance were not accompanied by any decrease in PAI-1 [21].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our 1-year results are in accordance with those previously obtained in a Swedish study [20]. In connection with the weight decline, our subjects' insulin sensitivity improved, which may partly explain the reduction in PAI-1 [30]. Surprisingly, there is one lifestyle intervention study in which marked weight loss and a decrease in insulin resistance were not accompanied by any decrease in PAI-1 [21].…”
Section: Discussionsupporting
confidence: 91%
“…The decline of PAI-1 has been shown to be more closely related to changes in adipose tissue than to changes in insulin levels [31]. Several studies have shown decreased PAI-1 levels after weight loss [17,18,[30][31][32], and the decrease seems to depend on the magnitude of the weight loss [17]. Furthermore, the PAI-1 level has been shown to increase when weight is regained [31].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been found that PAI-1 activity/ antigen in plasma are positively and moderately associated with BMI. Moreover weight reduction substantially reduces plasma PAI-1 in obese people (47,48). It has been shown that inhibitors of PAI-1 reduce dietary fat-induced obesity in C57BL/6 mice.…”
Section: Nutrition Pai-1 and Obesitymentioning
confidence: 99%
“…We also explore the pharmacological disruption of the E2F-pRB interaction to release free E2F, which we hypothesize will attenuate PAI-1 transcription and hence its plasma level. Adipocytes are chosen for this study, because they are responsible for obesity, abundant in caveolae (20), highly sensitive to insulin (Ͼ200,000 receptors per cell) (21), the primary site for insulin resistance (22), and a major contributor of plasma PAI-1 in the obese (23).…”
mentioning
confidence: 99%